Effect of Alternaria blight on the seed yield of cauliflower (Brassica oleracea L.) (Bangladesh Journal of Agricultural Research, 2010)
Effect of Alternaria blight (Alternaria brassiceae and A. brassicicola) on seed yield of cauliflower (Brassica oleracea L. var. botrytis) was studied during three consecutive growing seasons (2003-2004, 2004-2005, and 2005-2006) in winter under natural epiphytotic condition. There were two treatments viz. sprayed and unsprayed. BARI Cauliflower-1 was used as planting material and Rovral 50 WP (Iprodion) at 0.2% suspension was used as protective chemical to safe the crop against Alternaria brassiceae and A. brassicicola. Percent pod infection, pod area diseased, number of pods/plant and seed yield differed significantly between the sprayed and unsprayed (control) plots. Percent pod infection and pod area diseased ranged 35.3-62.4% and 94.7-97.6%, 1.9-2.2%, and 10.8-16.4% in sprayed and unsprayed plots in different, respectively. The number of pod/plant was 462-592 in sprayed and 281-395 in unsprayed plots. The seed yield/ha ranged 249.4-355.1 kg in unsprayed plots and 456.8-677.0 kg in Rovral sprayed plots. The seed yield increase were 59.6%, 171.4%, and 75.2% in 2003-2004, 2004-2005, and 2005-2006 cropping seasons, respectively. Keywords: Alternaria blight; seed yield; cauliflower.DOI: 10.3329/bjar.v35i3.6444Bangladesh J. Agril. Res. 35(3) : 381-385